Heart Rate and Extracellular Sodium and Potassium Modulation of Gap Junction Mediated Conduction in Guinea Pigs - Entz, Michael; George, Sharon A.; Zeitz, Michael J.; Raisch, Tristan; Smyth, James W.; Poelzing, Steven (Frontiers in Physiology, 2016)
Background: Recent studies suggested that cardiac conduction in murine hearts with narrow perinexi and 50% reduced connexin43 (Cx43) expression is more sensitive to relatively physiological changes of extracellular potassium ([K+]o) and sodium ([Na+]o). Purpose: Determine whether similar [K+]o and [Na+]o changes alter conduction velocity (CV) sensitivity to pharmacologic gap junction (GJ) uncoupling in guinea pigs. Methods: [K+]o and [Na+]o were varied in Langendorff perfused guinea pig ventricles (Solution A: [K+]o=4.56 and [Na+]o=153.3 mM. Solution B: [K+]o=6.95 and [Na+]o=145.5 mM). Gap junctions were inhibited with carbenoxolone (CBX) (15 and 30 μM). Epicardial CV was quantified by optical mapping. Perinexal width was measured with transmission electron microscopy. Total and phosphorylated Cx43 were evaluated by western blotting. Results: Solution composition did not alter CV under control conditions or with 15M CBX. Decreasing the basic cycle length (BCL) of pacing from 300 to 160ms decreased CV uniformly with both solutions. At 30 M CBX, a change in solution did not alter CV either longitudinally or transversely at BCL=300ms. However, reducing BCL to 160ms caused CV to decrease more in hearts perfused with Solution B than A. Solution composition did not alter perinexal width, nor did it change total or phosphorylated serine 368 Cx43 expression. These data suggest that the solution dependent CV changes were independent of altered perinexal width or GJ coupling. Action potential duration was always shorter in hearts perfused with Solution B than A, independent of pacing rate and/or CBX concentration. Conclusions: Increased heart rate and GJ uncoupling can unmask small CV differences caused by changing [K+]o and [Na+]o. These data suggest that modulating extracellular ionic composition may be a novel anti-arrhythmic target in diseases with abnormal GJ coupling, particularly when heart rate cannot be controlled.